PBN - Portugal, beekeeping and nosema - Pires, Sancia (2012)
This work aims at carrying out a survey to assess the prevalence of Nosema sp in Portugal. There has been an increasing number of positively lab-identified cases of Nosema in Bee Pathology Laboratories across the country in recent years. However, the optical microscopy methods that have been used are unreliable to identify the species of Nosema. Considering the growing number of reports implicating Nosema ceranae in colony morbidityl mortality, it is relevant to clarify the current epidemiology of Nosemosis in our specific national beekeeping context, pinpointing the etiologic agents to the species level and, eventually, identifying possible intra-specific types. We will also investigate the negative impact of Nosema on infected colonies and clarify t he efficacy of some biological commercially available products "recommended" to mitigate the impact of Nosema in honey bee colonies.